2005
DOI: 10.1148/rg.256055036
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary Mucinous Neoplasm of the Pancreas: Can Benign Lesions Be Differentiated from Malignant Lesions with Multidetector CT?

Abstract: Intraductal papillary mucinous neoplasm (IPMN) of the pancreas is a distinct clinicopathologic entity that is being recognized with increasing frequency. In 25%-44% of IPMNs treated with surgical resection, associated invasive carcinoma has been reported. Surgical resection is the treatment of choice for most IPMNs. Preoperative determination of the presence or absence of associated invasive carcinoma is crucial. The prognosis is worse if there is associated invasive carcinoma; when invasive carcinoma is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 39 publications
3
45
0
3
Order By: Relevance
“…14, 15 The presence of calcification within the tumour was evaluated on non-enhanced CT. We considered intratumoural calcification when high attenuating foci in the tumour (visually opaque as bone or .200 HU) was noted.…”
Section: 12mentioning
confidence: 99%
“…14, 15 The presence of calcification within the tumour was evaluated on non-enhanced CT. We considered intratumoural calcification when high attenuating foci in the tumour (visually opaque as bone or .200 HU) was noted.…”
Section: 12mentioning
confidence: 99%
“…The primary advantage of cross-sectional imaging such as CT scan and magnetic resonance (MR) of pancreatic cystic lesions over endoscopic techniques lies in determining the extent of malignant spread (39,40). Features predictive of invasive carcinoma in IPMN by CT and other imaging studies include involvement of the main pancreatic duct, marked dilatation of the main pancreatic duct, diffuse or multifocal involvement, the presence of a large mural nodule or solid mass, large size of the mass, and obstruction of the common bile duct.…”
Section: Imaging (Level 2-3)mentioning
confidence: 99%
“…Features predictive of invasive carcinoma in IPMN by CT and other imaging studies include involvement of the main pancreatic duct, marked dilatation of the main pancreatic duct, diffuse or multifocal involvement, the presence of a large mural nodule or solid mass, large size of the mass, and obstruction of the common bile duct. The presence of intracystic mural nodules >3 mm in size on CT also suggests malignancy (39)(40)(41). MRP is more sensitive than ERCP in differentiating mural nodules from mucin globules (40)(41)(42)(43)(44).…”
Section: Imaging (Level 2-3)mentioning
confidence: 99%
“…In MD IPMNs, ERCP shows dilated ducts and a filling defect caused by mucin or the cysts themselves, while in BD IPMNs the involved branches show dilation and communicate with the main duct (Lim et al, 2001). It has been reported that ERCP showed the communication of the cystic lesion with the pancreatic duct in 80.8% of the cases while MRCP showed 55.7%, CT showed 53.8%, and MRI showed 42.3% (Kawamoto et al, 2005). Another advantage of ERCP is that cytological sampling can be required, though it is an invasive procedure.…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp)mentioning
confidence: 99%